Cladocerans from gut contents of fishes associated to macrophytes from Taquari River Basin, MS, Brazil - Güntzel, Adriana Maria; Melo, Ilze Katsue Morita; Roche, Kennedy Francis; Silva, Valéria Flávia Batista da; Pompiani, Priscila Gusmão (Acta limnológica brasiliensia, 2012)
AIM: The aim of this study was to identify the cladocerans species from the gut contents of fishes sampled in an oxbow lake from Taquari River Basin, MS, with the specific view of investigating the importance of these crustaceans in the fishes diets; METHODS: Sampling was carried out in April and August of 2005 (dry season) and January of 2006 (wet season). The fish were captured with a sieve. In the laboratory, individuals were identified and stomachs were removed and weighed. The stomach contents were identified, and a Feeding Index calculated; RESULTS: The items most consumed by fishes were filamentous algae, Cladocera and detritus. The Cladocera were especially important in the August and January samples, and consisted primarily of Chydoridae; cladocerans were most consumed by species of Serrapinnus and by Mesonauta festivus. Fish fed more in April, with decreases occurring in stomach fullness on the other two sampling dates. CONCLUSIONS: Cladocerans associated with macrophytes may be an important food source for small fish individuals in marginal lakes from Taquari River Basin. The relative importance of the Chydoridae in the guts may have been due to the high relative abundance and species richness of this group in the environment. A short discussion on fish feeding habits was included in the text. OBJETIVO: Este estudo teve por objetivo identificar as espécies de cladóceros presentes no conteúdo estomacal de peixes amostrados em uma lagoa marginal da Bacia do Rio Taquari, MS, visando avaliar a importância destes crustáceos na dieta dos peixes; MÉTODOS: A amostragem foi realizada em abril e agosto de 2005 (estação seca) e janeiro de 2006 (estação chuvosa). Os peixes foram capturados com um peneirão. Em laboratório, os indivíduos foram identificados até o nível de espécie e os estômagos removidos e pesados. O conteúdo estomacal foi identificado e um Índice Alimentar calculado. RESULTADOS: Os itens mais consumidos pelos peixes foram algas filamentosas, Cladocera e detritos. Os Cladocera foram especialmente importantes em agosto e janeiro e consistiram principalmente de espécies de Chydoridae; os cladóceros foram mais consumidos por espécies de peixes do gênero Serrapinnus e por Mesonauta festivus. CONCLUSÕES: Cladóceros associados a macrófitas podem ser uma importante fonte de alimento para peixes de pequeno porte em lagoas marginais da Bacia do Rio Taquari. A importância relativa de Chydoridae nos estômagos deve ter sido devida elevada abundância relativa e riqueza de espécies deste grupo de cladóceros no ambiente. Uma pequena discussão sobre os hábitos alimentares das espécies de peixes encontradas na lagoa foi incluída no texto.